Analisis Komparasi Performa Bohlam LED Berbagai Merk - Rahman Azis Prasojo; Hafiz Furqoni; Muhammad Fahmi Hakim; Hari Kurnia Safitri; Heri Sungkowo (Elposys: Jurnal Sistem Kelistrikan, 2020)
LED bulb are increasingly being adopted not only because of their good efficacy, but also because they are known to have high controllability. LED lighting has developed rapidly in recent years to achieve more efficient and reliable LED performance. Several studies have conducted experiments to obtain the characteristics and performance of LED lamps. However, study comparing the performance of LED bulbs with various manufacturer and considering the price factor has not been found. In this study, the performance comparison of six LED bulb manufacturers that are commonly found in the Indonesian market were conducted. Each brand is sampled from three rated powers. The results of this study show a weak correlation between the price and performance. Nonetheless, the performance of LED bulb from different manufacturers were observed.